2015
DOI: 10.1371/journal.pone.0121075
|View full text |Cite
|
Sign up to set email alerts
|

Introgression Threatens the Survival of the Critically Endangered Freshwater Crayfish Cherax tenuimanus (Decapoda: Parastacidae) in the Wild

Abstract: Hybridization and genetic introgression following the introduction of exotic species can pose a significant threat to the survival of geographically restricted species. A remnant population of the critically endangered freshwater crayfish Cherax tenuimanus in the upper reaches of the Margaret River in southwestern Australia is under threat following the introduction and spread of its congener Cherax cainii. Here, we examine the extent of hybridization and introgression between the two species using twelve poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Hybridisation between these congeneric marron species has been confirmed (Austin and Ryan, 2002;Bunn et al, 2008;Kennington et al, 2014;Guildea et al, 2015), but it has been suggested that there are partial reproductive barriers present as levels of introgression are lower than would be predicted under random mating (Guildea et al, 2015). The partial reproductive barriers could be explained by the difference in timing of breeding seasons: although the mating seasons of both species overlap, C. cainii mate and reproduce earlier in the season than C. tenuimanus.…”
Section: Implications For Ex Situ Conservationmentioning
confidence: 95%
See 3 more Smart Citations
“…Hybridisation between these congeneric marron species has been confirmed (Austin and Ryan, 2002;Bunn et al, 2008;Kennington et al, 2014;Guildea et al, 2015), but it has been suggested that there are partial reproductive barriers present as levels of introgression are lower than would be predicted under random mating (Guildea et al, 2015). The partial reproductive barriers could be explained by the difference in timing of breeding seasons: although the mating seasons of both species overlap, C. cainii mate and reproduce earlier in the season than C. tenuimanus.…”
Section: Implications For Ex Situ Conservationmentioning
confidence: 95%
“…Only recently recognised as separate species, the highly restricted C. tenuimanus and its widespread sister-species C. cainii have experienced introgressive hybridisation, with hybrids producing fertile offspring (Austin and Ryan, 2002;Duffy et al, 2014;Guildea et al, 2015); hence, it was assumed that they require similar conditions for successful breeding. C. cainii has been a popular aquaculture species with a long history of captive breeding in Western Australia (Morrissy, 1970(Morrissy, , 1979Morrissy et al, 1990;Huner, 1994;Lawrence, 2007), and requirements for captive breeding (such as food, water quality, environmental parameters, stocking densities, etc.)…”
Section: Implications For Ex Situ Conservationmentioning
confidence: 99%
See 2 more Smart Citations
“…We detected two F 1 hybrids in this study, both involving sympatric species from quite different evolutionary lineages (G. brevipinnis and G. truttaceus, Site 24; G. truttaceus and G. oliros, Site 33) and neither identified a priori on the basis of external appearance. Unacknowledged introgression from widespread common species can seriously affect conservation efforts for rarer and narrowly distributed species (Guildea et al 2015;Frankham et al 2017), particularly if managers unwittingly choose only admixed populations for conservation management or as source populations for future translocations.…”
Section: Conservation Perspectivesmentioning
confidence: 99%